2016
DOI: 10.1007/s00167-016-4217-8
|View full text |Cite
|
Sign up to set email alerts
|

Saphenous nerve injury during hamstring tendons harvest: Does the incision matter? A systematic review

Abstract: Systematic review, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 24 publications
3
40
0
1
Order By: Relevance
“…Three main incisional approaches are currently used—horizontal, vertical, and oblique. The choice of one over the other has been a subject of contention among surgeons, since each carries its own specific benefits and risks (Ruffilli et al, ; Pękala et al, ). The goal of the present study was to use high‐resolution USG to locate the IPBSN and estimate the rate of injury for each of the three main incision types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three main incisional approaches are currently used—horizontal, vertical, and oblique. The choice of one over the other has been a subject of contention among surgeons, since each carries its own specific benefits and risks (Ruffilli et al, ; Pękala et al, ). The goal of the present study was to use high‐resolution USG to locate the IPBSN and estimate the rate of injury for each of the three main incision types.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we attempted to assess the risk of injury to the IPBSN in relation to the nerve's pattern of emergence. Recent systematic studies (Ruffilli et al, 2016;Pe R kala et al, 2017) have comprehensively reviewed the literature concerning iatrogenic injury to the IPBSN during hamstring tendon harvesting, seeking the safest incision type. Despite numerous publications on this topic, the study quality assessments by the authors of the two above-mentioned systematic reviews (Ruffilli et al, 2016;Pe R kala et al, 2017) concluded that most of the existing clinical studies can be described as methodologically poor or medium, so there is a need for new well-designed clinical trials and translational research.…”
Section: Discussionmentioning
confidence: 99%
“…При заборе сухожилий подколенных мышц имеется риск повредить две чувствительные ветви подкожного нерва -поднадколенниковая ветвь (иннервирует кожу переднемедиальной и переднелатеральной поверхностей коленного сустава) и портняжная терминальная веточка (идет вертикально по медиальной поверхности коленного сустава за портняжной мышцей, затем перфорирует фасцию между сухожилиями неж-ной и портняжной мышц и иннервирует кожу внутренней поверхности голени и голеностопного сустава) [25].…”
Section: Review Articles and Lecturesunclassified
“…The IBSN supplies sensory innervation to the anteromedial aspect of the knee and the SBSN continues along the great saphenous vein to provide sensation to the medial aspect of the lower leg 6 . Iatrogenic nerve damage may cause hypoesthesia, dysesthesia, painful neuroma, reflex sympathetic dystrophy, anterior knee pain and kneeling pain 7 .…”
Section: Introductionmentioning
confidence: 99%